Peran Kepercayaan Sebagai Mediasi Hubungan Identifikasi Tim dan Konflik - Windra Laksana Putra; Enggar Sulistiyono (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
Conflict plays an important role in work organizations where good conflict management can benefit the organization as a whole. The purpose of this study was to examine the relationship between trust, team identification and conflict in teams both task conflict and relationship conflict. The study also examined the effect of the relationship between team identification and conflict in teams with trust in colleagues as mediators. This research is an empirical research with a quantitative descriptive approach. This research uses a case study model involving 252 employees at a maufaktur company and 219 employees at a large pharmaceutical company in the Central Java region. The findings showed that team identification was associated with lower levels of relationship conflict and task conflict. These relationships are mediated by trust in their co-workers The findings reveal concerns about the mechanisms by which employee attitudes influence performance behavior. The research also shows how managers and organizations create optimal levels of conflict in their teamwork.